IPO Stock Performance amidst the COVID-19 Pandemic: Has It been Undervalued? - Randy Kuswanto (Jurnal Dinamika Akuntansi dan Bisnis, 2021)
The purpose of this study is to examine the underpricing phenomenon from IPO firms listed in Indonesia Stock Exchange during the COVID-19 pandemic. Using purposive sampling method, 34 IPO firms after the announcement of pandemic COVID-19 were selected as research samples. The IPO stock closing prices and returns on days 1, 5, 10, 15, and 20 were analyzed using paired sample t-test. The findings show underpricing phenomenon still occurred during the pandemic period. However, the underpricing only documented statistically significant on the T1 of the trading day. After the first day of trading, the stock’s returns consistently declined and were proved statistically insignificant at T5, T10, T15, and T20.